A Review of European Owls as Predators of Bats - Mikkola, Heimo Juhani (2019)
Fossil evidence indicates that owls have been preying on bats from as far back as the Pleistocene. Overall, bats form quite small portions (i.e. trace to 0.2%) of the diets (by prey frequency) of European owls. An assessment of dietary studies and anecdotal accounts reveals that five species of European owls, the Eurasian scops owl Otus scops, Pygmy owl Glaucidium passerinum, Tengmalm‚Äôs owl Aegolius funereus, little owl Athene noctua and Ural owl Strix uralensis, rarely feed on bats (with less than 0.1‚àí0.4%) and a further two species, short-eared owl Asio flammeus and eagle owl Bubo bubo, may only take bats occasionally, while three species, long-eared owl Asio otus, barn owl Tyto alba and tawny owl Strix aluco, feed on bats more frequently. In this study, a total of 19,864 recorded bats have been preyed upon by these owls, with as many as 48 bat species being identified. Barn and tawny owls have captured most of this total (47.1 and 41.9%), followed by the long-eared owl (7.6%), while short-eared and eagle owls take similar amounts of bats (1.1 and 1.7%, respectively). Owl predation on bats deserves future research because it may help contribute to our knowledge on bat biodiversity and distribution and possibly identify an additional risk for small populations of endangered bats.